Intervention for Developmental Speech Sound Disorders in YouTube Videos: Parent Perceptions and Clinical Utility. - Bellon-Harn, Monica L.; Morris, Lekeitha R.; Gilmore, Carolyn N.; Smith, Chloe (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: This study investigated how parents of children with developmental speech sound disorders perceive the understandability, actionability, and credibility of YouTube videos related to speech therapy and explored how they utilize the internet and social media platforms to inform their understanding of their child's disorder . Method: A mixed-methods design was used. First, YouTube videos were extracted, coded, and analyzed for understandability and actionability. The five highest ranked and five lowest ranked videos comprised the data set. Parents viewed and rated the videos on understandability, actionability, and credibility. The Wilcoxon matched-pairs, signed-ranks test was used to analyze the differences between high- and low-rated videos. Parents participated in semistructured interviews about their use of social media platforms. Thematic analysis was used to explore the ways in which parents were utilizing social media platforms. Results: Parents rated high-quality YouTube videos significantly higher than low-quality videos across all dimensions of understandability, actionability, and credibility (p < .001). Their evaluations aligned with expert ratings, indicating that parents can discern content quality effectively. Qualitative analysis revealed that parents valued speech-language pathologists (SLPs) as their primary and most trusted source of information. Online content, while often used for supplemental learning, was seen as less reliable, with parents expressing concerns about credibility, specificity, and practical applicability. Parents expressed that watching other families and their children was beneficial because it provided hope and shared experiences. Conclusion: Parents are capable of distinguishing high- from low-quality videos but still overwhelmingly rely on SLPs for trusted, individualized guidance.